The Influence of Prior Knowledge on Students’ Listening and Reading Comprehension - Abdullah Hasan; Rizky Gushendra; Ferri Yonantha (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACTThe research aims to investigate the influence of prior knowledge on students’ listening and reading comprehension at the tenth year of MAN 1 Pekanbaru. This study is a correlational research that involved 75 respondents as a sample from 150 students of the the tenth year of Science classes as the total population. The respondents were selected by using a simple random sampling technique. 20 items of multiple choice of listening test and 20 items of multiple choice of reading test and 15 items of the prior knowledge questionnaire were used to collect the data. Afterwards, the data were further analyzed by using Pearson product moment correlation for the first and the second hypotheses and MANOVA (Multivariate Analysis of Variance) for the third hypothesis by using SPSS 25. The research findings revealed that the mean score of students’ prior knowledge is 73.41 and is categorized as “Good”, their listening comprehension is 68.13 and is categorized as “Good”, and their reading comprehension is 70.67 and it is also categorized as “Good”. It can be seen that the value of Sig. (2-tailed) is 0.000<0.05. Lastly, for the third hypothesis, the value of significance is 0.000<0.05. It means Ha is accepted. Then, it is generated that there is a significant influence of prior knowledge on both students’ listening comprehension and reading comprehension.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh pengetahuan yang ada pada siswa terhadap pemahaman listening dan speaking siswa kelas X MAN 1 Pekanbaru. Kajian ini merupakan penelitian korelasi yang terdiri dari 75 responden sebagai sampel dari populasi 150 orang siswa kelas X jurusan IPA dengan menggunakan tehnik sampel acak. tes Listening dan Reading menggunakan pilihan ganda yang masing-masingnya terdiri dari 20 soal. Kuesioner digunakan untuk mengumpulkan data. Kuesioner ini terdiri dari 15 pernyataan. Selanjutnya data dianalisa dengan menggunakan korelasi Pearson Product Moment untuk hipotesis yang pertama dan kedua, sedangkan untuk menganalisa hipotesis yang ketiga menggunakan MANOVA (Multivariate Analysis of Variance) SPSS versi 25. Hasil penelitian mengungkapkan nilai rata-rata pengetahuan yang sudah ada adalah 73.41 dan dikategorikan “Baik”. Nilai rata-rata listening comprehension 68.13 dan dikategorikan “Baik” serta nilai rata-rata reading comprehension 70.67 dan juga dikategorikan “Baik” Dapat diketahui bahwa nilai signifikan (2;tailed) adalah 0.000<0.05. Akhirnya, untuk hipotesa yang ketiga nilai signifikannya 0.000<0.05. Hasil ini menunjukkan bahwa Ha diterima. Kemudian, disimpulkan bahwa terdapat pengaruh yang signifikan prior knowledge siswa terhadap listening dan reading comprehension. How to Cite: Hasan, A. Gushendra, R. Yonantha, F. (2017). The Influence of Prior Knowledge on Students’ Listening and Reading Comprehension. IJEE (Indonesian Journal of English Education), 4(1), 1-15 doi:10.15408/ijee.v4i1.4744.DOI: http://dx.doi.org/10.15408/ijee.v4i1.4744